2003
DOI: 10.1097/00001756-200308060-00007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal behavior: activation of the central oxytocin receptor system in parturient rats?

Abstract: Parturition plays a critical role in the full expression of maternal behavior in postpartum females, yet the precise mechanism remains unclear. Here we examined the role of parturition in the activation of Fos and FosB in the central oxytocin receptor (OTR) system in rats. Although expression of FosB, not Fos, was seen in the piriform cortex (Pir) and caudate putamen of virgin and pregnant females, activation of Fos and FosB with extensive co-localization was found in the medial preoptic area, the bed nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Estrogens have been shown to increase both prolactin receptor and OTR expression or affinity (3,33), which might explain the facilitating effect of estrogens on ma- on May 12, 2018 by guest http://mcb.asm.org/ ternal care. It has also been shown that rat strains with good mothering qualities express more OTRs in the MPOA than other strains (7,11) and that parturition enhances c-fos and fosB expression in OTR-positive hypothalamic neurons (20). These findings suggest that OTR-mediated activation or modulation of MPOA neurons play a central role in the induction of maternal care.…”
Section: Discussionmentioning
confidence: 93%
“…Estrogens have been shown to increase both prolactin receptor and OTR expression or affinity (3,33), which might explain the facilitating effect of estrogens on ma- on May 12, 2018 by guest http://mcb.asm.org/ ternal care. It has also been shown that rat strains with good mothering qualities express more OTRs in the MPOA than other strains (7,11) and that parturition enhances c-fos and fosB expression in OTR-positive hypothalamic neurons (20). These findings suggest that OTR-mediated activation or modulation of MPOA neurons play a central role in the induction of maternal care.…”
Section: Discussionmentioning
confidence: 93%
“…Parturition induces Fos immunoreactivity in OTR-immunoreactive neurons within the rat piriform cortex (Lin et al, 2003). Furthermore, fMRI shows activation of the piriform cortex by suck- Figure 8.…”
Section: Piriform Cortexmentioning
confidence: 98%
“…For example, it has been documented that there is an increase in the level of corticosterone (Atkinson and Waddell, 1995), hippocampal spine densities, and activation of the oxytocin and vasopressin systems during the postpartum period (Caba et al, 1996; Lin et al, 2003). Recently, interest has emerged to investigate the effect of parenthood on adult neurogenesis (Leuner et al, 2010a; Levy et al, 2011).…”
Section: Effect Of Adult–offspring Interactions On Adult Neurogenesismentioning
confidence: 99%